An investigation into the exchange rate volatility of Malaysia: assessing asymmetry and persistency - Fardous, Alom (2014)
This study attempts to examine the asymmetry and persistency of exchange rate volatility of Malaysian Ringgit against U.S. dollar, British pound, Euro, Japanese yen, and Singapore dollar within the framework of asymmetric component GARCH models using daily data over the period of 1 August, 2005 to 24 April, 2014. The empirical findings reveal mixed evidence vis-à-vis asymmetry and persistency of exchange rate shocks to the volatility of Malaysian currency against different currencies considered in the study. The estimated results exhibit that the volatility of Malaysia’s exchange rate returns can be modelled with GARCH-type conditional variance models where models capture volatility characteristics well. The shocks of volatility to the Malaysia’s exchange rate are found to be highly persistent against USD while those are found to be reasonably persistent against Euro, British pound, Singapore dollar and Japanese yen. Asymmetric effects of shocks to the volatility of Malaysia’s exchange rate against USD, Euro and Japanese yen is evidenced implying positive and negative shocks pose different effects to rise or fall of the volatility while symmetric effect of shocks to the volatility is recorded for British Pound and Singapore dollar. The empirical findings of this study provide insights to the policymakers and practitioners.